FACTORS INFLUENCING THE EMPLOYEE PERFORMANCE IN TELECOMMUNICATIONS INDUSTRY OFMALDIVES - Aminath, Shaznie; Aishath, Sinaau (INTI International University, 2023)
This research will aim to determine the influence between workplace health and safety practices and employee performance in telecommunication industry of Maldives. Telecommunication industry of Maldives is evolving and the job opportunities in the industry is booming. There is limited research done in the Maldives to identify how OHS practices influence employee performance in the sector. Hence, the objective of this study is to determine whether there is a relationship between OHS practices and employee performance in the telecommunication sector of Maldives. To gain insight into the subject, a number of publications and journals were studied for the literature review. Researchers concurred that there are challenges with the topic that make it difficult to see the situation clearly. Quantitative research methodology will be employed for this study, and both primary and secondary sources will be consulted. Using stratified sampling, a sample size of 88 will be chosen for the primary research from a population of 113. A questionnaire will be employed in this study's correlative research design, and the HR teams of the participating firms will help disseminate it to participants in order to collect data. With the aid of SPSS, cross tabulations and correlation will be used to examine the data. This proposal includes introduction into the research, literature review and the proposed methodology for the research.